Keanekaragaman Hayati Indonesia: Masalah dan Upaya Konservasinya (Badan Pengembang Konservasi UNNES, 2022)
The purpose of this study is to describe the current diversity of flora and fauna, to analyze and describe the factors that cause the decline in Indonesia's biodiversity, to analyze and describe the efforts that have been made by Indonesia to maintain biodiversity and to analyze and describe the challenges facing Indonesia in increasing its efforts to enhancement of biodiversity benefits. The research was conducted using a library search method. Data were collected from competent institutions and analyzed descriptively. Indonesia has a high diversity of flora and fauna. Of the 1,812,700 species that have been described in the world, 31,750 (1.75%) species are found in Indonesia, even the moss group exceeds 10%. For fauna, Indonesia occupies the second place in fauna wealth after Brazil, about 12% of mammals, 16% of reptiles, and 17% of the world's birds are found in Indonesia. Meanwhile, in terms of mammals and amphibians, Indonesia ranks fifth and sixth. Indonesia is also famous for its diversity of coastal ecosystems, which contain 18 percent of the world's coral reefs, more than 70 genera and 500 coral species, 2,500 fish species, 2,500 mollusc species, 1,500 crustacean species, and various other marine biota. However, Indonesia is also considered a country with a high decline in diversity. Indonesia has 583 species that are threatened with extinction, including 191 species of mammals and 160 species of birds. As an effort to preserve biodiversity, Indonesia has established a conservation area of 46,279,090.10 ha, consisting of 27,134,394.79 terrestrial conservation areas and 19,144,695.28 marine conservation areas and protects 904 species, consisting of 787 fauna and 117 flora. Most of Indonesia's biodiversity data (23.98%) is obtained based on exploration results in Java, which covers only 6.76% of Indonesia's area, so that with extensive exploration outside Java, it is estimated that Indonesia's biodiversity will continue to increase. To increase the benefits of biodiversity, Indonesia's future challenges include increasing the effectiveness of conservation and bioprospecting efforts.